Butterfly Effect: Satu Hal Kecil Yang Merubah Hidup Sepenuhnya - Santoso, Gunawan; Restu M Hasbylah; Cholichul Hadi; Masduki Asbari; Meilanta Rantina (Yayasan Aya Sophia Indonesia, 2023)
Tujuannya adalah untuk memahami pandangan Restu M Hasbylah dari channel YouTube 1 Hari Sukses tentang